A critical reflection of current trends in discourse analytical research on leadership across disciplines. A call for a more engaging dialogue. (August 2019) - Schnurr, Stephanie; Schroeder, Andreas
This paper takes the frequently lamented state of current leadership research in business and organisational sciences as a starting point and argues for a more open and engaging dialogue with leadership researchers in applied linguistics and pragmatics. Focusing on current debates around terminological issues and methodological questions that are particularly prominent in critical leadership studies, we show that research in applied linguistics and pragmatics has the potential to make important contributions by providing the analytical tools and processes to support critical leadership researchers in their quest to challenge hegemonic notions of leadership by moving beyond simplistic and often problematic leader–follower dichotomies and by providing empirical evidence to capture leadership in situ thereby feeding into current theorisations of leadership.